Manejo de conflictos laborales en el Gad Municipal del cantón Saquisilí – 2023. - Tigsi Gaglay, Miryam Verónica (2023)
Labor conflicts constitute an element of impact in the environment of public and private organizations and inevitably affect productivity and the service they provide, influencing the perception of their workplace. In this sense, the objective of the present research project was to analyze labor conflicts in the Municipal GAD of the Saquisilí canton, Cotopaxi Province. For this, it used a descriptive quantitative methodology, which provide information on the characteristics of the studied population. The information gathering tool is a questionnaire created by ROCCI II, consisting of 27 questions, with a Likert rating scale from 1 to 4, with 1 being never and 4 always. The questionnaire was applied in person to 100 employees that make up the Municipal GAD of the Saquisilí Canton; The interview created by Clara Toro, a student at the Simón Bolívar Andean University, was applied to 6 directors of the aforementioned institution. The application of the instruments allows the implementation of strategies that strengthen the work environment. The results obtained show that the institution has a minimum percentage of labor conflicts. However, in light of the differences that some officials have also expressed, we went on to develop ways that can help enhance how the institution's environment is perceived by its users.